IMPLEMENTATION OF LOCAL REGULATION NO.11 OF 2006 CONCERNING GUIDELINES FOR THE ESTABLISHMENT OF VILLAGE CONSULTATIVE BODIES IN KECAMATAN BANDUNGAN KABUPATEN SEMARANG (Study Implementation Of Tupoksi BPD - Maria Ulfa; Zainal Hidayat (Journal of Public Policy and Management Review, 2019)
Village consultative body or abbreviated as BPD formed based on the district regulation of Semarang regency No.11 of 2006 concerning guidelines for establishing village consultative bodies. The regulation concerning the establishment of the BPD and the tasks carried out by the village consultative body (BPD). Kecamatan Bandungan is a sub-district in the district of Semarang which in each village has formed a village consultative body (BPD) and has implemented its tasks, principal functions. The purpose of this study was to find out how the implementation of the main task and function of the village consultative bodies (BPD), as well as the factor affecting of the implementation. This research used descriptive method-qualitative approach. The result of this study indicate that village consultative bodies (BPD) in the Kecamatan Bandungan have four functions : legislative function, the supervisory function, the budget function and the aspiration function. Of the four functions carried out by BPD already implemented but for legislatve function and supervisory functions there are still many shortcoming and least maximized. Affecting factor of the implementation are communication, cooperation, activeness and participation of members, facilities and level of education.